The 'policy mix' for innovation: Rethinking innovation policy in a multi-level, multi-actor context - Kieron Flanagan; Elvira Uyarra; Manuel Larangja (The University of Manchester, Manchester Business School, 2010)
Recent years have seen the emergence, take-up and use of the term 'policy mix' by innovation policy makers and by policy analysts & scholars alike. Imported from economic policy debates, the term implies a focus on the interactions and interdependencies between different policies as they affect the extent to which intended policy outcomes are achieved. However the meaning of the term remains ambiguous. Nonetheless, we argue that the emergence of the 'policy mix' concept into common use in the field of innovation policy studies provides us with a window of opportunity to reconsider some basic and often hidden assumptions in order to better deal with a messy and complex, multi-level, multi-actor reality. We draw on the mainstream policy studies literature and on evolutionary thinking in order to re-conceptualise the basic building blocks of innovation policy studies in order to arrive at a useful definition of 'policy mix' interactions. We suggest that this reconceptualisation has profound implications for the scope and focus of innovation policy studies and for what such studies can realistically hope to achieve in terms of policy prescriptions.
Keywords: 330; policy mix; policy interactions; policy instruments; actors; agency; innovation policy